S30 TRUSS is a regulator of TNFα-TNF-R1 induced NF-κB activation. (16th November 2010) - Horan, I P; Langton, A J; Farrow, S; Riches, D W; Chilvers, E R; Parfrey, H
Abstract : Introduction: TNFα is a pleiotropic cytokine that can exert opposing biological actions, either pro-inflammatory or pro-apoptotic, through interaction with its cognate receptor TNF-R1. How this balance is regulated remains to be elucidated. One possible regulator is the novel TNF-R1 interacting protein TRUSS (TNF-R1 ubiquitous signalling and scaffold protein). Ectopic expression of TRUSS activates the transcription factors NF-κB and AP-1. Aims: To determine the physiological role of TRUSS in TNFα-TNF-R1 signal transduction. Methods: Human epithelial (A549) cells were transfected with human TRUSS siRNA and responses to TNFα stimulation were assessed by RT-PCR, ELISA, immunoblotting and confocal microscopy. Results: TRUSS knockdown impaired secretion of the inflammatory chemokines IL-6 and IL-8 following prolonged TNFα stimulation. The maximal reduction of IL-8 mRNA and protein occurred after 12 h of TNFα incubation in the TRUSS deficient cells (p<0.03), whereas the IL-6 responses were decreased after 24 h (p<0.03) (Abstract S30 Figure 1 ). Furthermore, these effects were abrogated by cycloheximide or the NF-κB inhibitor Bay11-7085, indicating that the inflammatory chemokines were newly synthesised in response to TNFα stimulation via an NF-κB dependent pathway. The upstream signalling molecules TNFR1, TRADD, TRAF2 and RIP were unaffected by TRUSS deficiency. However, phosphorylation of the p50 precursor p105 was augmented in the cytosolic fraction of TRUSS knockdown cells whilst total p50 in the nuclear fraction was reduced by TNFα stimulation. This was associated with impaired nuclear translocation of the activated NF-κB subunit p65 and enhanced JNK phosphorylation. Conclusions: Our data suggest TRUSS is integral to TNFα-TNF-R1 mediated NF-κB activation. We propose that TRUSS functions as a scaffold protein involved in the proteasomal processing of p105 into the p50 subunit. Inhibition of this process impairs the nuclear translocation of NF-κB and the consequent p65/p50 regulated gene transcription. Hence, TRUSS may be a novel target for modulating the inflammatory functions of TNFα-TNF-R1 signalling.